Recurrent Ischemic Stroke and Bleeding in Patients With Atrial Fibrillation Who Suffered an Acute Stroke While on Treatment With Nonvitamin K Antagonist Oral Anticoagulants: The RENO-EXTEND Study. Issue 8 (11th May 2022) - Paciaroni, Maurizio; Caso, Valeria; Agnelli, Giancarlo; Mosconi, Maria Giulia; Giustozzi, Michela; Seiffge, David Julian; Engelter, Stefan T.; Lyrer, Philippe; Polymeris, Alexandros A.; Kriemler, Lilian; Zietz, Annaelle; Putaala, Jukka; et al.
Abstract : Background: In patients with atrial fibrillation who suffered an ischemic stroke while on treatment with nonvitamin K antagonist oral anticoagulants, rates and determinants of recurrent ischemic events and major bleedings remain uncertain. Methods: This prospective multicenter observational study aimed to estimate the rates of ischemic and bleeding events and their determinants in the follow-up of consecutive patients with atrial fibrillation who suffered an acute cerebrovascular ischemic event while on nonvitamin K antagonist oral anticoagulant treatment. Afterwards, we compared the estimated risks of ischemic and bleeding events between the patients in whom anticoagulant therapy was changed to those who continued the original treatment. Results: After a mean follow-up time of 15.0±10.9 months, 192 out of 1240 patients (15.5%) had 207 ischemic or bleeding events corresponding to an annual rate of 13.4%. Among the events, 111 were ischemic strokes, 15 systemic embolisms, 24 intracranial bleedings, and 57 major extracranial bleedings. Predictive factors of recurrent ischemic events (strokes and systemic embolisms) included CHA2 DS2 -VASc score after the index event (odds ratio [OR], 1.2 [95% CI, 1.0–1.3] for each point increase; P =0.05) and hypertension (OR, 2.3 [95% CI, 1.0–5.1]; P =0.04). Predictive factors of bleeding events (intracranial and major extracranial bleedings) included age (OR, 1.1 [95% CI, 1.0–1.2] for each year increase; P =0.002), history of major bleeding (OR, 6.9 [95% CI, 3.4–14.2]; P =0.0001) and the concomitant administration of an antiplatelet agent (OR, 2.8 [95% CI, 1.4–5.5]; P =0.003). Rates of ischemic and bleeding events were no different in patients who changed or not changed the original nonvitamin K antagonist oral anticoagulants treatment (OR, 1.2 [95% CI, 0.8–1.7]). Conclusions: Patients suffering a stroke despite being on nonvitamin K antagonist oral anticoagulant therapy are at high risk of recurrent ischemic stroke and bleeding. In these patients, further research is needed to improve secondary prevention by investigating the mechanisms of recurrent ischemic stroke and bleeding.